Literaturoznawstwo jako roz-twarzanie. Problem podwójnego autorstwa w tekstach Tadeusza Rachwała i Tadeusza Sławka - Bogalecki, Piotr (Wydawnictwo Naukowe UAM, 2007)
The essay is an attempt of rethinking a mode of authorship in literary science discourse of Tadeusz Rachwał and Tadeusz Sławek. Their texts is being compared with G. Deleuze and F. Guattari's method of collective writing and interpreted according to theories of J. Derrida, P. de Man and M. Foucault. Rachwał and Sławek's strategy of double authorship (which is not the same as traditional co-authorship) underlines the impossibility of recognition who is speaking in the text; therefore their collective books may be understood as a kind of performing theses which they contain (e.g. connected with poststructuralist "death of author" or a poet and God's mystical co-writing). Furthermore, double authorship leaves its marks on structure of text. We can see a lot of techniques which make Rachwał and Sławek's texts more complicated, e.g. fragmentary style of writing, using different types of typography and even creating an elements of visual poetry. These experiments and a new way of these texts' being in academic public sphere make them rather ethical than scientific - the ethic qualities and poetic function seem to be more important than the science typical cognitive functions. Because of unceasing underlining a linguistic aspect, the texts of Rachwał and Sławek may be read as examples of rhetorical type of ethic criticism. Not only do they ask about a significance of primary ethical ideas like friendship, community or responsibility, but also about an existence of category of author in literary studies after linguistic turn.
The literary science as de-facement. Problem of double authorship in Tadeusz Rachwał and Tadeusz Sławek's texts